Leader-Member Exchange, Quality of Worklife, Working Satisfaction and Organizational Citizenship Behavior - I Gede Artha Kesumawijaya; A.A.N. Oka Suryadinatha Gorda (Jurnal Manajemen dan Bisnis, 2016)
Organizational Justice, and Quality of Work life toward Organizational Citizenship Behaviormediated by Job Satisfaction of the employee of Bali Regional Office of the Ministry of Lawand Human Rights.Respondents of this research were 136 government employees in Bali Regional Office ofthe Ministry of Law and Human Rights. The sampling technique that was census, and thedata were analyzed using Structural Equation Modeling (SEM) by occupying AMOSprogram. The result of this research shows that Leader-Member Exchange gives positive andsignificant effect toward Job Satisfaction. The same results also applied on Leader-MemberExchange toward Organizational Citizenship Behavior, Organizational Justice toward JobSatisfaction, Organizational Justice toward Organizational Citizenship Behavior, Quality ofWork life toward Job Satisfaction, Quality of Work life toward Organizational CitizenshipBehavior, Job Satisfaction toward Organizational Citizenship Behavior. This research alsofound out that Job satisfaction significantly mediating the effect of Leader-MemberExchange, Organizational Justice , Quality of Work life toward Organizational CitizenshipBehavior.Managerial implication of this research would be the stakeholders which consists ofstructural official or the leaders who supposed to do evaluation and also improving the use ofLeader-Member Exchange, Organizational Justice, dan Quality of Worklife in order toimprove Job Satisfaction and also Organizational Citizenship Behavior of Bali RegionalOffice of the Ministry of Law and Human Rights’ employee.Keywords : Leader-Member Exchange, Organizational Justice, Quality ofWorklife, Job Satisfaction, and Organizational Citizenship Behavior.